2014
DOI: 10.1088/0957-4484/25/37/371001
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength of carbyne chains in varied chemical environments and structural lengths

Abstract: Carbyne and carbyne-based low-dimensional structures are promising for several applications including ultra-compact circuits and purification devices. Designing any applied carbyne-based structure requires a fundamental understanding of the mechanical strength of carbyne chains with different lengths at different temperatures and operating chemical environment. Here we use molecular dynamics simulations to investigate the strength of carbyne chains with different lengths at different temperatures. A theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Molecular dynamics under a microcanonical ensemble was used by Mirzaeifar et al [19] to study the strength of carbon chains of different dimensions at a variable temperature. It was found that the presence of H2O molecules improves the bond stability, resulting in higher values of mechanical Nowadays it is difficult to synthesize monoatomic carbon chains in any form.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Molecular dynamics under a microcanonical ensemble was used by Mirzaeifar et al [19] to study the strength of carbon chains of different dimensions at a variable temperature. It was found that the presence of H2O molecules improves the bond stability, resulting in higher values of mechanical Nowadays it is difficult to synthesize monoatomic carbon chains in any form.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This force field has been used to study the mechanics of carbyne chain in different solvent conditions and shows good agreement with DFT calculations. 13,25,26 The mechanical response of two …”
mentioning
confidence: 99%
“…4,8−12 Its constituent building block, carbyne, is a one-dimensional carbon allotrope that shows chemical stability in water environment in a wide range of temperatures. 1,13,14 Moreover, one type of graphyne material besides graphene has been successfully synthesized 11 and its mechanical strength can reach 50 GPa, 10 which is on the same order of magnitude as graphene 15,16 and suggesting applications for fast water filtration. However, considering that the loading force generated from the viscous drag is proportional to the throughput (vD 2 , as schematically shown in Figure 1a), the occurrence of water flow at a nanoscale pore can lead to forces that would easily exceed the material strength and rupture even materials as strong as graphene or graphyne.…”
mentioning
confidence: 99%
See 2 more Smart Citations